2001
DOI: 10.1111/j.1469-7793.2001.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NADPH oxidase‐related proton and electron currents in human eosinophils by arachidonic acid

Abstract: 1. Effects of arachidonic acid (AA) on proton and electron currents in human eosinophils were studied using the permeabilized-patch voltage-clamp technique, using an applied NH 4 + gradient to control pH i .2. Superoxide anion (O 2 _ ) release was assessed by cytochrome c reduction in human eosinophils. Significant O 2 _ release was stimulated by 5-10 µM AA.3. AA activated diphenylene iodinium (DPI)-inhibitable inward current reflecting electron efflux through NADPH oxidase. These electron currents (I e ) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 45 publications
6
119
0
2
Order By: Relevance
“…For this reason, significant results can be obtained with cell lines that are usually considered devoid of superoxide-generating systems (9,10), such as T lymphocytes (Jurkat) and undifferentiated HL-60 cells, as shown here. "Professional" superoxide-generating cells, such as macrophages and PMN-differentiated HL-60 cells, showed the greatest capacity for NBT reduction, but the production of superoxide was also clearly demonstrated in lymphocytes, even without cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, significant results can be obtained with cell lines that are usually considered devoid of superoxide-generating systems (9,10), such as T lymphocytes (Jurkat) and undifferentiated HL-60 cells, as shown here. "Professional" superoxide-generating cells, such as macrophages and PMN-differentiated HL-60 cells, showed the greatest capacity for NBT reduction, but the production of superoxide was also clearly demonstrated in lymphocytes, even without cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that AA might act as a detergent, but its effect must involve other mechanisms as well, as Many theories have been proposed to explain AA stimulation of the oxidative burst. In the PMA-stimulated NADPH system, it could cause dissociation of inhibitors of components of the NADPH complex, promote an ideal membrane environment for enzyme function, promote the phosphorylation or translocation of p47 phox (15,23,25), stimulate the NADPH oxidase proton pump (10,26), activate or promote PKC translocation (12,23,(27)(28)(29), stimulate the cell, mimicking, when in the micellar state, particulate stimuli (14,22), or stimulating the cell via the generation of eicosanoids (6). Regarding the mitochondrial-derived superoxide production, AA could act by its known mitochondrial uncoupling ability (carrying protons across the inner mitochondrial membrane), stimulating the opening of the permeability transition pore or acting as a prooxidant, and affecting electron transport (10,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Although originally thought to be part of the NADPH oxidase complex, the proton channel now appears to be a distinct protein that is, nevertheless, concomitantly regulated by PKC (DeCoursey et al, 2001a). Stimuli such as arachidonic acid and PMA, which activate the proton channels in neutrophils and eosinophils, also stimulate electron transport through the oxidase (DeCoursey et al, 2000;DeCoursey et al, 2001b;Cherny et al, 2001). Although PMAstimulated NADPH oxidase activity can be blocked with the PKCδ selective inhibitor, rottlerin, the proton conductance is insensitive to PKCδ inhibition (Bankers-Fulbright, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent results obtained in neutrophils (Jankowski and Grinstein, 1999). Although several groups have described the presence of proton channels in eosinophils (Gordienko et al, 1996;Schrenzel et al, 1996;Bánfi et al, 1999;Bankers-Fulbright et al, 2001;Cherny et al, 2001;DeCoursey et al, 2001a;DeCoursey et al, 2001b), the membrane potential determined by current clamp measurements indicated that depolarization following activation of NADPH oxidase was not sufficient to activate the proton channel (Gordienko et al, 1996;Tare et al, 1998;Bánfi et al, 1999). Eosinophil resting membrane potential has been reported to be between -60 and -80 mV (Gordienko et al, 1996;Tare et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation